Screening and routine diagnosis of mental disorders among migrants in primary care: A cross-sectional study - Stella Evangelidou; Angeline Cruz; Yolanda Osorio; Ethel Sequeira-Aymar; Alessandra Queiroga Gonçalves; Laura Camps-Vila; Marta M. Monclús-González; Alba Cuxart-Graell; Elisa M. Revuelta-Muñoz; Núria Busquet-Solé; Susana Sarriegui-Domínguez; Aina Casellas; et al. (Elsevier, 2023)
Background: Migrants in host countries are at risk for the development of mental health conditions. The two aims of the study were to describe routine diagnoses of mental disorders among migrant patients at primary healthcare level and the associated risk factors, and to test the utility of an innovative migrant mental health assessment by evaluating whether the health professionals followed the recommendations proposed by the clinical decision support system (CDSS) tool. Methods: A cross-sectional study was carried out in eight primary care centres (PCCs) in four non-randomly selected health regions of Catalonia, Spain from March to December 2018. Routine health data and mental health diagnoses based on the International Classification of Diseases (10th edition), including mental, behavioural and neuro developmental disorders (F01-F99), symptoms and signs involving emotional state (R45), and sleep disorders (G47), were extracted from the electronic health records. The proportion of mental health conditions was estimated and logistic regression models were used to assess any possible association with mental health disorders. The utility of the mental health assessment was assessed with the proportion of questionnaires performed by health professionals for migrants fulfilling the mental health screening criterion (country of origin with an active conflict in 2017) and the diagnoses given to the screened patients. Results: Of 14,130 migrants that visited any of the PCCs during the study period, 7,358 (52.1 %) were women with a median age of 38.0 years-old. There were 520/14,130 (3.7 %) migrant patients diagnosed with a mental disorder, being more frequent among women (342/7,358; 4.7 %, p-value < 0.001), migrants from Latin-America (177/3,483; 5.1 %, p < 0.001) and those who recently arrived in Spain (170/3,672; 4.6 %, p < 0.001). A lower proportion of mental disorders were reported in migrants coming from conflicted countries in 2017 (116/3,669, 3.2 %, p = 0.053).Out of the 547 mental health diagnoses reported in 520 patients, 69/14,130 (0.5 %) were mood disorders, 346/14,130 (2.5 %) anxiety disorders and 127/14,130 (0.9 %) sleeping disorders. Mood disorders were more common in migrants from Eastern Europe (25/2,971; 0.8 %, p < 0.001) and anxiety disorders in migrants from Latin-America (126/3,483; 3.6 %, p < 0.001), while both type of disorders were more often reported in women (p < 0.001).In the adjusted model, women (aOR: 1.5, [95 % CI 1.2-1.8, p < 0.001]), migrants with more than one visit to the health center during the study period (aOR: 4.4, [95 %CI 2.8-6.8, p < 0.001]) and who presented an infectious disease (aOR: 2.1, [95 %CI 1.5-3.1, p < 0.001]) had higher odds of having a mental disorder.Lastly, out of the 1,840 migrants coming from a conflicted country in 2017 who were attended in centres where the CDSS tool was implemented, 29 (1.6 %) had a mental health assessment performed and the tool correctly identified one individual. Conclusions: Mental health is a condition that may be overlooked in migrants at primary healthcare. Interventions at this level of care must be reinforced and adapted to the needs and circumstances of migrants to ensure equity in health services.